Wach modules, regulator maps, and [epsilon]-isomorphisms in families - Bellovin, Rebecca; Venjakob, Otmar (International mathematics research notices, 2019)
Abstract. We prove the “local epsilon-isomorphism” conjecture of Fukaya and Kato [13] for certain crystalline families of $G_{{Q_p}}$-representa
Published: 06 November 2017
Gesehen am 25.11.2019
Im Titel ist "epsilon" als griechischer Buchstabe dargestellt